FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN KERJA DAN PENGARUHNYA TERHADAP PENGUNDURAN DIRI KARYAWAN (STUDI KASUS: FEMINAGROUP) - Amanda Setiorini (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
The aim of this study is to determine factors that lead to job satisfaction and its impact to resignation. This study consists of two submodels. The first submodel investigate the influence of compensation, job security, career path , organizational communication, and company policy on job satisfaction. While the second submodel investigate the effect of job satisfaction of the employee's resignation. The first submodel found that compensation and job security variables have no significant effect on job satisfaction, while career paths, organizational communication, and company policies have a significant impact on job satisfaction. The results of submodel 2 states that job satisfaction have a significant effect on the employee's resignation. Relationships are both negative, which means if the job satisfactions are high, the resignation will be lower. And vice versa.